861 Successfully implementing information systems to improve occupational health and safety performance – 2: case studies. (24th April 2018) - Jones, D; Darwin, L; Wilson, K; Kisting, S; Spiegel, JM; Adu, P; Yassi, A
Abstract : Introduction: With over 7400 employees in 346 laboratories and 3 national institutes across South Africa, the National Health Laboratory Service (NHLS) faces the challenge of how to provide occupational health, biosafety and biosecurity services with limited resources. The Occupational Health and Safety Information System (OHASIS) was initially developed at the University of British Columbia in Canada as a multi-modular, secure online information system and is now a joint venture with South Africa's National Institute for Occupational Health. Methods: By reviewing 6 years of OHASIS and health and safety program implementation at NHLS, including surveying of users, we provide a qualitative and quantitative summary of experience, including presentation of illustrative cases, and discuss the strengths and limitations of using a comprehensive information system to improve occupational health and safety. Results: Online surveys (2013 and 2015) indicated an overall improvement in many areas of health, biosafety and biosecurity including training, trust of management, reporting incidents, use of Personal Protective Equipment and participation in committees. Over 1600 incidents have been recorded, with increased usage following introduction of a confidential self-report mechanism. This has enabled systematised reviews by health and safety committees, the Safety, Health and Environment team and NHLS management. In addition to existing modules (e.g. incident reporting and investigation; employee health; analytics), new modules have been added in response to user requests: Audits; Waste; Maintenance; and Training. A strategic new module on Health and Safety Committees is currently underway. Discussion: Surveys and discussions reveal a need for ongoing attention to implementation. Analysis of trends and associations is being emphasised as long term sustainability solutions are being sought, especially in response to the widespread interest for introducing OHASIS in other settings. The National Institute for Occupational Health has the exclusive rights to roll OHASIS out throughout Africa.